Selected Leaf Diseases of Rubber: Symptoms and Control – A Review - Oghama, O. E.; Omorusi, V. I.; Osazuwa, E. S. (Journal of Applied Sciences and Environmental Management, 2023)
This paper is a review article with the objective of providing valuable, recent and solid information and critical understanding of symptoms and control of selected leaf diseases of rubber tree (Hevea brasiliensis Muell. Arg) using secondary information and data harvested from previously published studies found online. Data gathered showed that H. brasiliensis is subject to a plethora of economically important diseases mainly of fungal origin, classified as leaf, stem and branch, panel and root disease. Some fundamental causal organisms of leaf diseases in H. brasiliensis includes Pseudocercospora ulei, Oidium heveae, Colletotrichum gloeosporioides and Corynespora cassiicola. Corynespora leaf fall caused by Corynespora cassiicola is currently accepted as the leaf disease which causes about 45% of yield loss to rubber in mostly Asian and African continents. The symptoms of South American Leaf Blight (SALB) range from discoloration of lamina to death of tree when untreated. Leaf disease symptoms range from white powdery patches to shriveling and falling off of tender leaves and translucent brownish yellow spots in semi-matured leaves in Oidium leaf disease. Colletotrichum leaf disease symptoms range from necrosis of tender leaves of young plants to defoliation and death of entire plant. Disease control is achieved by the use of chemicals and planting of disease-resistant varieties. Some phylloplane fungi are prospective biological control agents. The best treatment to manage Corynespora leaf fall disease (CLFD) in nurseries is the introduction of overhead shading coupled with application of the fungicide mancozeb. Diseases affecting the leaves of H. brasiliensis can be devastating and can lead to loss of multiple rubber trees and reduction in the latex production of the trees. Therefore, adequate preventive, curative and control measures against the diseases should be taking to ensure maintenance of a healthy rubber tree plantation.